2020
DOI: 10.1590/2179-8087.026318
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Regimes on Growth and Metabolic Processes of Enterolobium contortisiliquum Seedlings

Abstract: In forest nurseries, one of the factors that change the growth and quality of seedlings is water supply, which has a direct influence on metabolic processes such as stomatal conductance and photochemical efficiency of photosystem II. This study aims to identify the influence of different watering regimes as well as the use of a water-retaining polymer on the initial growth and metabolic processes of Enterolobium contortisiliquum seedlings. The experimental design was in random blocks with a factorial scheme. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…On the other hand, Turchetto et al (2020) observed that in the production of Enterolobium contortisiliquum seedlings, irrigation regimes of 8 and 12 mm day -1 are necessary to obtain adequate development. Dutra et al (2018) found that Luehea divaricata seedlings submitted to different substrates and irrigation schemes had high water demand during the production phase, requiring 16 mm day -1 of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Turchetto et al (2020) observed that in the production of Enterolobium contortisiliquum seedlings, irrigation regimes of 8 and 12 mm day -1 are necessary to obtain adequate development. Dutra et al (2018) found that Luehea divaricata seedlings submitted to different substrates and irrigation schemes had high water demand during the production phase, requiring 16 mm day -1 of water.…”
Section: Discussionmentioning
confidence: 99%
“…et Zucc (Dutra et al 2018) and Enterolobium contortisiliquum (Vell.) Morong (Turchetto et al 2020), have shown the importance of aligning daily irrigation levels with the characteristics of the species and stage of nursery growth. According to Dutra et al (2018) identifying regimens suitable for different species will aid in reducing seedling production costs as well as providing superior physiological and sanitary control.…”
Section: Introductionmentioning
confidence: 99%
“…Mattos seedlings production, also found the positive effect of adding 4.0 g L -1 hydrogel to the substrate on growth in height and diameter of the collection. Turchetto et al (2020), evaluating the effect of different substrates and irrigation regimes on morphophysiological attributes of Enterolobium contortisiliquum seedlings, observed that hydrogel incorporation to the substrate provides higher growth rates and biomass allocation, regardless of the daily water regime adopted.…”
Section: Discussionmentioning
confidence: 99%
“…This polymer have the capacity to absorb water during periods of water availability and release it to the roots of plants when there is a deficit in the soil (Leciejewski, 2009). Previous studies have already shown positive effects of hydrogel on tree nursery-grown seedling development (Griebeler et al, 2022;Turchetto et al, 2020). However, studies that evaluate its effectiveness in direct sowing of forest species are scarce (Souza, 2022).…”
Section: Introductionmentioning
confidence: 99%